Proposed Design of a Wireless Communication Network ForWater Management Applications in Mosul City - S. Alsharbaty, Firas; Y. Abdullah, Fawaz; Tariq Yaseen, Mohammad (Iraqi Journal for Electrical and Electronic Engineering, 2026)
Water scarcity, drought, and population growth accompanying climate change are dangerous factors with seriousconsequences related to potable water file unless appropriate action is taken urgently to deal with these issues, especiallywith large populations in the major cities as well as the suburban areas. This work presents an enhanced wide areanetwork for efficient management of the freshwater in the major cities. Hence, it adopts Mosul city as a typical casethat contains about 100 residential districts that require 100 sites of water monitoring in the different locations in thecity where each site owns three different types of water sensors (water flow, water level, and pressure) in addition to thevideo surveillance application. The water station sites send the data to the control and monitoring center of the water.The collected data is processed and analyzed by public cloud or private cloud for control and monitoring purposes. Thesuggested communication network addresses the requirements of the water section applications in terms of monitoring inreal-time. This work addresses the WiMAX system as a communication network infrastructure to handle the advantagesof resilience, low-cost maintenance, and expansion The suggested network offered excellent behavior in terms of latency(maximum latency is less than 57 msec) and data traffic of the adopted applications.